Reliable and easy-to-use calculating tool for the Nail Psoriasis Severity Index using deep learning - Hiroto Horikawa; Keiji Tanese; Naoki Nonaka; Jun Seita; Masayuki Amagai; Masataka Saito (npj Systems Biology and Applications)
Abstract Since nail psoriasis restricts the patient’s daily activities, therapeutic intervention based on reliable and reproducible evaluation is critical. The Nail Psoriasis Severity Index (NAPSI) is a validated scoring tool, but its usefulness is limited by interobserver variability. This study aimed to develop a reliable and accurate NAPSI scoring tool using deep learning. The tool “NAPSI calculator” includes two parts: nail detection from images and NAPSI scoring. NAPSI was annotated by nine nail experts who are board-certified dermatologists with sufficient experience in a specialized clinic for nail diseases. In the final test set, the “NAPSI calculator” correctly located 137/138 nails and scored NAPSI with higher accuracy than the compared six non-board-certified residents: 83.9% vs 65.7%; P = 0.008 and four board-certified non-nail expert dermatologists: 83.9% vs 73.0%; P = 0.005. The “NAPSI calculator” can be readily used in a clinical situation, contributing to raising the medical practice level for nail psoriasis.